2011
DOI: 10.1103/physrevb.84.245305
|View full text |Cite
|
Sign up to set email alerts
|

Calculated electron affinity and stability of halogen-terminated diamond

Abstract: The chemical termination of diamond has a dramatic impact on its electrical and chemical properties, where hydrogen and oxygen termination produce negative and positive electron affinities, respectively. However, the impact of halogen termination is not fully understood. We show that for low-index surfaces, 100% fluorinated surfaces exhibit chemically stable positive electron affinities in the 1.17 to 2.63 eV range, whereas 100% chlorination is energetically unfavorable. At lower coverage the positive electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 47 publications
13
74
0
Order By: Relevance
“…Previous theoretical calculations show that fluorine adsorption energy remains low for all coverages, meaning it is possible to have a full monolayer of F on a diamond h100i surface, whereas full and stable coverage is less likely for other terminations, such as Cl. 10 In summary, we demonstrated that fluorine-termination from CF 4 plasma treatments yields a higher NV À population than oxygen-termination, which is currently used for all magnetometry and photonic diamond devices. From our photoluminescence data on H-, O-, and F-terminated surfaces with nearby NVs, we observe a correlation between the surface dipole strength and the ratio of negatively charged NV centers to neutrally charged NVs.…”
Section: Increased Negatively Charged Nitrogen-vacancy Centers In Flumentioning
confidence: 99%
See 1 more Smart Citation
“…Previous theoretical calculations show that fluorine adsorption energy remains low for all coverages, meaning it is possible to have a full monolayer of F on a diamond h100i surface, whereas full and stable coverage is less likely for other terminations, such as Cl. 10 In summary, we demonstrated that fluorine-termination from CF 4 plasma treatments yields a higher NV À population than oxygen-termination, which is currently used for all magnetometry and photonic diamond devices. From our photoluminescence data on H-, O-, and F-terminated surfaces with nearby NVs, we observe a correlation between the surface dipole strength and the ratio of negatively charged NV centers to neutrally charged NVs.…”
Section: Increased Negatively Charged Nitrogen-vacancy Centers In Flumentioning
confidence: 99%
“…Ab initio calculations of fluorinated diamonds show a stable and full coverage of F, as well as a high electron affinity. 10 Recently, the fluorinated diamond electron affinity has been measured experimentally to be 2.56 eV, about 0.43 eV higher than for the oxygenterminated surface. 11 Various methods have been reported in the literature for fluorine-terminating diamond surfaces, including exposure to XeF 2 gas, 11,12 CF 4 plasma, 13 and CHF 3 plasma.…”
Section: Increased Negatively Charged Nitrogen-vacancy Centers In Flumentioning
confidence: 99%
“…25 Furthermore, the experimentally determined electron affinity for F:C(100) is considerably higher than the value of 2.13 eV recently predicted by density functional theory calculations. 21 FIG. 2.…”
mentioning
confidence: 99%
“…17,18 Ab initio calculations state that the 1.0 ML coverage of F is very stable in the 2 Â 1 reconstruction with a C-C bond length of 1.61 Å for neighbouring atoms in the dimer and a fluorine atom bonded to each of these carbons with a C-C-F bond angle of 109.6 . 21 The large difference in electronegativity between fluorine and carbon, 3.98 and 2.55, respectively, on the Pauling scale, means the C-F bond is highly polar and will give rise to a very high electron affinity even compared to that of Oterminated diamond on account of the potential step associated with the C dþ À F dÀ dipole layer at the surface. However, despite its potential application to a number of fields, the electronic properties of the F-terminated diamond surface remarkably are not known.…”
mentioning
confidence: 99%
“…H-termination in diamond forms heteropolar C-H bonds yielding H with a negative charge (surface side) and C with a positive charge (film side) helping to reduce the work function of the material. [32][33][34][35][36][37][38] This effect is reduced in films of smaller grain size due to a larger fraction of sp 2 C on their surface in comparison to MCD, resulting in a lower responsivity in Region C for SMCD and NCD. Figure 4(b) illustrates schematically the source of photoelectrons within the band diagram of diamond responsible for the responsivities obtained in Regions A, B, and C. We examine electron escape probability (Equation (3)) from the diamond surface with v negative electron affinity and illuminated with radiation of energy h .…”
mentioning
confidence: 99%